Acidic oxide molecular sieve hierarchical pore catalytic material as well as preparation method and application thereof
By loading acid oxide on the H-ZSM-5 multi-stage pore carrier to form a catalyst with a multi-stage pore structure, the mass transfer resistance and stability problems of existing catalysts in biodiesel production are solved, and efficient and stable biodiesel production is achieved.
Patent Information
- Application Number
- CN202411661049.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
In the production of biodiesel, existing catalysts have problems such as mass transfer resistance, poor thermal stability, and difficulty in recycling, especially when dealing with macromolecular greases, they are inefficient and prone to inactivation.
A multi-stage pore catalytic material of acid oxide molecular sieve was developed to form a catalyst with a macroporous-mesoporous-micropore structure by loading WO3 or WO3 and MoO3 onto the H-ZSM-5 multi-stage pore support, thereby improving catalytic performance and stability.
This catalyst can effectively reduce the mass transfer limit of macromolecular oils and fats, improve biodiesel production efficiency, and have good coke formation resistance and reusable performance.
Smart Images

Figure CN119500245A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomass conversion and application, and in particular to an acidic oxide molecular sieve multi-level pore catalytic material and a preparation method and application thereof. Background Art
[0002] Biodiesel is produced by transesterification of oil (triglyceride) with methanol or esterification of long-chain fatty acid with methanol, and its component is long-chain fatty acid methyl ester. In the industrial production of biodiesel, one of the important challenges is the high cost of raw materials, which accounts for about 75-80% of the total cost of biodiesel production. In order to make biodiesel production economical, reliable and sustainable, waste oil (such as frying oil, waste oil, etc.) is considered to be the most preferred raw material in biodiesel production. However, waste oil usually contains a large amount of free fatty acids (FFAs) and water, which can cause serious deactivation of the catalyst. Solid acid catalysts are suitable for such waste oils. Due to their low sensitivity to FFAs and water, there is no need to eliminate FFAs and water from waste oils during the preparation of biodiesel. At the same time, solid acid catalysts can simultaneously catalyze the transesterification of triglycerides and the esterification of FFAs, thereby realizing one-pot conversion of waste oils into biodiesel.
[0003] Hierarchical porous materials are a new type of advanced solid catalyst carrier, which contains two or more pore structures. Because of their rich pore structure and large specific surface area, hierarchical porous materials can be applied in many fields. In the process of producing biodiesel by oil transesterification (triglyceride transesterification), the oil molecules are large and there is a large mass transfer resistance, which is a great challenge for the design of catalysts. The apparent activity of heterogeneous catalysts is determined by the inherent activity of the catalytic center, the availability of the active center and the surface mass transfer properties. The pore size distribution and coherence of the catalyst have an important influence on its specific surface area, the availability of the active center and the mass transfer rate. In the catalytic process, mesopores and micropores can provide a larger specific surface area, the macroporous structure can increase the mass transfer rate of the reaction substrate, and the interpenetrating hierarchical pore structure network can enhance the utilization of the active center and reduce the mass transfer resistance of the material. Most of the existing industrial catalysts are microporous structures, and there are mass transfer barriers for macromolecules. Therefore, in view of the mass transfer problem of oil macromolecules (triglyceride macromolecules), designing and synthesizing catalysts with hierarchical pore structures is an effective method to improve the catalytic efficiency.
[0004] Catalysts play an important role in the preparation of biofuels. It is of great significance to develop efficient, low-cost and easy-to-prepare catalysts. Compared with homogeneous catalytic systems, heterogeneous solid catalysts are easy to separate from products and can be reused. In solid catalysts, the structure and characteristics of the carrier have an important influence on the performance of the catalyst. However, existing solid catalysts have defects in porosity, structural uniformity, stability and specific surface area. Especially for the conversion reaction of biomass macromolecules, existing catalysts have surface mass transfer resistance problems, resulting in low catalytic activity, and are prone to carbon deposits, which deactivate the catalyst.
[0005] Currently, most reported zeolite molecular sieve catalysts exhibit microporous or mesoporous pores. When used as catalysts for biodiesel production, they are not conducive to the circulation and diffusion of oil macromolecules on the catalyst surface, which will cause an increase in mass transfer resistance. In addition, there are problems such as poor thermal stability of zeolite nanocrystals, easy destruction, and difficulty in recovering from the reaction mixture. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a multi-level pore molecular sieve solid acid catalytic material with a macroporous structure, which can reduce the transmission and diffusion restrictions of macromolecular oil reactants, has better resistance to coke formation, improves the catalytic performance of the catalytic material in oil conversion, and can especially convert waste oil into biofuel in one step, improve biofuel production efficiency, and has good stability and recyclability. Therefore, the present invention provides an acidic oxide molecular sieve multi-level pore catalytic material and its preparation method and application in the preparation of biofuel from oil, especially in the preparation of biofuel from waste oil.
[0007] Specifically, the technical solution adopted by the present invention is:
[0008] An acidic oxide molecular sieve multi-level porous catalytic material comprises an H-ZSM-5 multi-level porous carrier and an acidic oxide loaded on the H-ZSM-5 multi-level porous carrier, wherein the H-ZSM-5 multi-level porous carrier is a zeolite with an ordered macropore-mesopore-micropore multi-level porous structure, and the acidic oxide mainly comprises WO3 or mainly comprises WO3 and MoO3.
[0009] The molar ratio of the metal element in the acidic oxide to the silicon element in the H-ZSM-5 multi-level porous carrier is 0.1-0.2.
[0010] Furthermore, the acidic oxide is mainly composed of WO3 and MoO3, and the molar ratio of WO3 to MoO3 is 1:1-1.2.
[0011] In the present invention, when the acidic oxide is mainly composed of WO3, the acidic oxide molecular sieve multi-level porous catalytic material is represented by W@H-ZSM-5; when the acidic oxide is mainly composed of WO3 and MoO3, the acidic oxide molecular sieve multi-level porous catalytic material is represented by MoW@H-ZSM-5.
[0012] The acidic oxide molecular sieve multi-level pore catalytic material has a macropore-mesopore-micropore multi-level pore structure and a surface area of 290-310 m 2 / g, pore volume is 0.10-0.11cm 3 / g, the average pore size is 4.61-4.82nm, and the acid content is 1-1.2mmol / g.
[0013] The specific surface area of the H-ZSM-5 multi-level pore carrier is 400-500m 2 / g, pore volume is 0.12-0.18cm 3 / g, and the average pore size is 4.87-9.18nm.
[0014] The present invention also provides a method for preparing the above-mentioned acidic oxide molecular sieve multi-level porous catalytic material, comprising the steps of:
[0015] Impregnation treatment: using an acidic oxide precursor and a H-ZSM-5 multi-level porous carrier as raw materials, the acidic oxide precursor is loaded onto the H-ZSM-5 multi-level porous carrier by an impregnation method to obtain H-ZSM-5 loaded with the acidic oxide precursor; wherein the acidic oxide precursor mainly includes H3PO4·12WO3·XH2O, or mainly includes H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 ·4H2O mixture;
[0016] Calcination treatment: The H-ZSM-5 loaded with the acidic oxide precursor is calcined at 500-700° C. to obtain the acidic oxide molecular sieve multi-level pore catalytic material.
[0017] During the calcination process, the precursors H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 4H2O is decomposed to form acidic oxides WO3 and MoO3. To ensure that the acidic oxide precursor is completely calcined and decomposed, the calcination time is preferably 6-10 hours.
[0018] In order to completely decompose the acidic oxide precursor and avoid the undesirable aggregation of the acidic oxide active components as much as possible, the calcination treatment step includes: calcining the H-ZSM-5 loaded with the acidic oxide precursor at 550-600°C for 6-10 hours to completely convert the loaded acidic oxide precursor into the acidic oxide, thereby obtaining the above-mentioned acidic oxide molecular sieve multi-level pore catalytic material. The calcination time is preferably 7-9 hours.
[0019] The impregnation step includes: impregnating the H-ZSM-5 multi-level porous support into an acidic oxide precursor solution for 8-12 hours by an impregnation method, and then performing a drying process to obtain the H-ZSM-5 loaded with the acidic oxide precursor. The drying process temperature is preferably 80-100° C., and the drying time is preferably 12-24 hours.
[0020] In order to ensure that the acidic oxide precursor is completely dissolved in water to form the acidic oxide precursor solution, the mass ratio of the acidic oxide precursor to water is 1:4-10, preferably 1:5-7.
[0021] In order to better exert the activity of the acidic oxide in the catalytic center, the molar ratio of the metal element of the acidic oxide precursor to the silicon element in the H-ZSM-5 multi-level porous carrier is preferably 0.1-0.2, represented by X. Therefore, the above-mentioned acidic oxide molecular sieve multi-level porous catalytic material provided by the present invention can be represented by XW@H-ZSM-5-Y or X MoW@H-ZSM-5-Y, wherein Y represents the calcination temperature in the calcination treatment step.
[0022] Wherein, when the acidic oxide precursor is H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 ·4H2O, due to the synergistic effect, the W element in H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 The molar ratio of the Mo element to 4H2O is preferably 1:1-1.2.
[0023] Furthermore, the preparation method of the H-ZSM-5 multi-level porous carrier includes: using mesoporous silica balls (MSPs) as templates and preparing them by thermal evaporation induced self-assembly method. Specifically, the MSPs and Al(NO3)3·9H2O solution are uniformly mixed, and then dried at 30-50°C for 2-4h to obtain MSPs dry powder loaded with aluminum nitrate; the dry powder is uniformly mixed with a tetrapropylammonium hydroxide (TPAOH) aqueous solution with a concentration of 30wt%-50wt% at 30-60°C for 1.5-3h to deposit aluminum hydroxide on the MSPs in situ, and crystallization treatment is performed under the assistance of thermal evaporation for 48-72h, and then filtered, and dried at 70-100°C for 12-24h to obtain MSPs loaded with aluminum hydroxide; then, the MSPs loaded with aluminum hydroxide are calcined at a calcination temperature of 500-600°C for 4-6h to obtain a H-ZSM-5 multi-level porous carrier with a multi-level porous structure.
[0024] The particle size of the MSPs is 240-260 nm, and the specific surface area is 321-348 m 2 / g, pore volume is 0.12-0.14cm 3 / g.
[0025] If the amount of Al(NO3)3·9H2O is too large or too small, a H-ZSM-5 support with a stable structure cannot be obtained. Therefore, the mass ratio of MSPs to Al(NO3)3·9H2O is 1:3-3.5, preferably 1:3.05-3.15.
[0026] TPAOH mainly provides microporous template and alkalinity source for the formation of H-ZSM-5 hierarchical pore carrier; if its dosage is too large, there will be too many micropores; if it is too small, there will be insufficient alkali. Therefore, the mass ratio of MSPs to TPAOH aqueous solution is 1:1-1.5.
[0027] Further, the preparation method of the MSPs comprises: adding hexadecyltrimethylammonium bromide (CTAB) to an ethanol-water solution, stirring and dissolving, then adding a 25wt% ammonia solution, stirring at room temperature for 1-2h; then adding tetraethyl orthosilicate (TEOS), stirring at room temperature for 1-2h to obtain a white precipitate; the obtained precipitate is dried at 70-100°C overnight, and then calcined at 500-600°C for 6-8h to obtain mesoporous silica spheres. Wherein, the volume percentage of ethanol in the ethanol-water solution is 70%-80%, preferably 75%-78%; the amount of CTAB added is 1:60-65g / mL; the amount of 25wt% ammonia solution added is 4-8% of the volume ratio of ethanol-water solution, preferably 5-6%; the amount of TEOS added is 10%-20% of the mass of the ammonia solution, preferably 15%.
[0028] The present invention provides an application of the above-mentioned acidic oxide molecular sieve multi-level porous catalytic material in catalyzing oil to produce biofuel. Wherein, the oil can be pure oil or waste oil, and the pure oil includes vegetable oil, animal oil, etc. The vegetable oil can be soybean oil, peanut oil, melon seed oil, rapeseed oil, cottonseed oil, jatropha seed oil, etc. The water content in the waste oil is 0-5.8%, and the free fatty acid content is 0-62.7 mg (KOH) / g; it can be waste frying oil, waste kitchen oil, waste rancid oil, etc. The biofuel is biodiesel. Preferably, the amount of the acidic oxide molecular sieve multi-level porous catalytic material is 6-10wt% of the mass of the oil.
[0029] The above technical solution provided by the present invention has the following advantages:
[0030] (1) The acidic oxide molecular sieve multi-level porous catalytic material has a high specific surface area and a multi-level pore structure, wherein the macropores can increase the mass transfer capacity of oil molecules, and the mesopores and micropores can increase the specific surface area of the catalytic material;
[0031] (2) The acidic oxide molecular sieve multi-level pore catalytic material has and Lewis acid catalytic center, with a total acid content of 1-1.2mmol / g, suitable for efficient conversion of acid-catalyzed biomass macromolecules; has good acid and water resistance, and has the ability to simultaneously catalyze triglyceride transesterification (oil transesterification) and free fatty acid esterification; can convert vegetable oil and waste vegetable oil and other oils into biofuels in one step;
[0032] (3) The acidic oxide molecular sieve multi-level pore catalytic material is used as a catalyst, and waste oil and methanol are used as raw materials to convert triglycerides and free fatty acids in the waste oil into biofuels in one pot, without the need to perform deacidification and dehydration treatment on the waste oil in advance; the triglyceride conversion rate can reach 94%, and the free fatty acids can be completely converted into biofuels at the same time;
[0033] (4) The acidic oxide molecular sieve multi-level porous catalytic material MoW@H-ZSM-5 has good recycling performance as a catalyst for producing biofuels.
[0034] Therefore, the entire production process of producing biofuels using the above-mentioned acidic oxide molecular sieve multi-level porous catalytic material provided by the present invention as a catalyst with oil and methanol as raw materials has the characteristics of high yield, short process, and green process, and has industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1SEM images of the H-ZSM-5 multi-level porous carrier (a, b) and the MoW@H-ZSM-5 multi-level porous catalytic material (c, d) provided in Example 1 of the present invention, and SEM-Mapping image of the MoW@H-ZSM-5 catalyst;
[0036] Figure 2 TEM images of the H-ZSM-5 multi-level porous support (a, c) and the MoW@H-ZSM-5 multi-level porous catalytic material (b, d) provided in Example 1 of the present invention;
[0037] Figure 3 N2 adsorption-desorption curve diagram of the H-ZSM-5 multi-level porous carrier and MoW@H-ZSM-5 multi-level porous catalytic material provided in Example 1 of the present invention;
[0038] Figure 4 NH3-TPD curves of the H-ZSM-5 multi-level porous carrier and the MoW@H-ZSM-5 multi-level porous catalytic material provided in Example 1 of the present invention;
[0039] Figure 5 This is a Py-IR spectrum diagram of the MoW@H-ZSM-5 multi-level porous catalytic material provided in Example 1 of the present invention at different desorption temperatures. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0041] The terms used in the present invention are all commonly used in the field, and the raw materials, equipment, preparation processes, testing methods, etc. used are all prior art in the field unless otherwise specified. Specific implementation conditions and methods are not specified in each embodiment, and generally conventional conditions and methods are used.
[0042] The measurement method used in each embodiment is as follows:
[0043] Specific surface area measurement method: The specific surface area and pore size distribution of the sample were measured by nitrogen adsorption-desorption at 120°C for 8 hours using the American Micromeritics ASAP 2460 fully automatic specific surface and porosity analyzer. After the measurement, the specific surface area of the sample was calculated based on the experimental data using the BET formula, and the pore volume and pore size distribution were calculated using the BJH method.
[0044] Determination of oil conversion rate (triglyceride conversion rate): Agilent 7890N gas chromatograph was used for determination, and the detector was FID detector. In this method, methyl heptadecanoate was used as the internal standard, n-hexane was used as the solvent, and fatty acid methyl ester was determined based on the retention time of the reference standard. The oil conversion rate was calculated according to the following formula:
[0045]
[0046] In the above formula, X ME is the oil conversion rate, ∑A ME It can be defined as the total peak area of oil. As represents the peak area of the internal standard, Vs represents the volume of the internal standard, unit: mL; Cs represents the concentration of the internal standard, unit: mg / mL; m represents the mass of the sample, unit: mg.
[0047] Determination of free fatty acid conversion rate: The conversion rate of free fatty acid esterification is calculated based on the change ratio of the acid value of the substrate before and after the reaction. The determination of acid esters is carried out according to GB5530-85.
[0048] Example 1 MoW@H-ZSM-5 and its preparation method
[0049] This embodiment provides an acidic oxide molecular sieve multi-level porous material MoW@H-ZSM-5 and a preparation method thereof. The preparation method mainly includes the steps of preparing a multi-level porous structure carrier H-ZSM-5 and preparing the multi-level porous material MoW@H-ZSM-5.
[0050] S1: Preparation of mesoporous silica spheres: 2880 mL of ethanol and 830 mL of deionized water were mixed in a beaker, and then 60 g of CTAB was added to the ethanol-water solution and stirred to dissolve. After the dissolution was completed, 145 ml of 25 wt% ammonia solution was added and stirred at room temperature for 1.5 h; then 22 mL of TEOS was added, and the reaction solution was stirred at room temperature for 2 h to obtain a white precipitate; the obtained precipitate was dried at 80 ° C overnight. The dried solid was placed in a muffle furnace and calcined at 550 ° C for 6 h. 18.7 g of mesoporous silica spheres MSPs were obtained.
[0051] S2: Add 10g of MSPs to 32g of Al(NO3)3·9H2O solution, stir to mix, and dry at 40°C for 3h. Then, mix the dried powder with 14g of 40wt% TPAOH aqueous solution to obtain a mixed solution with a molar composition of 1SiO2:0.005Al2O3:0.16TPAOH. Then, impregnate MSPs at 40°C for 2h. After crystallization assisted by thermal evaporation for 54h, the solid product is recovered by filtration, washed with water and dried at 80°C for 18h. The dried sample is placed in a muffle furnace and calcined at 550°C for 5h, and finally 16.2g of a multi-level porous structure H-ZSM-5 multi-level porous carrier is obtained. Its specific surface area is measured to be 460.1m 2 / g, pore volume 0.12cm 3 / g, and the average pore size is 4.86nm.
[0052] S3: Preparation of acidic oxide molecular sieve multi-level pore MoW@H-ZSM catalytic material: 5.23g H3PO4·12WO3·XH2O and 3.83g (NH4)6Mo7O 24 ·4H2O was dissolved in 80mL water, 10g H-ZSM-5 multi-level porous carrier was added, and stirred at room temperature for 12h. Then it was filtered and dried at 80℃ for 18h to obtain loaded H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 ·4H2O H-ZSM-5. The dried loaded H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 ·4H2O H-ZSM-5 was placed in a muffle furnace and calcined at 550°C for 8h. Finally, 17.2g of MoW@H-ZSM multi-level porous catalytic material was obtained. In the multi-level porous catalytic material, the molar ratio of Mo to W was 1:1, and the total molar ratio of Mo / Si and W / Si was 0.13. The MoW@H-ZSM multi-level porous material provided in this embodiment can be marked as: 0.13MoW@H-ZSM-550°C.
[0053] Structure and performance characterization of hierarchical porous materials
[0054] (1) Scanning electron microscopy (SEM) analysis
[0055] In order to confirm the structure of the acidic oxide molecular sieve multi-level porous catalytic material, SEM analysis was performed on the H-ZSM-5 multi-level porous carrier prepared in Example 1 and the 0.13MoW@H-ZSM-550℃ multi-level porous catalytic material provided in Example 1. The results are as follows: Figure 1 shown.
[0056] The H-ZSM-5 multi-level pore carrier is a zeolite crystal with a good macropore structure. The macropore diameter is about 200-260nm, and the macropore structure is evenly distributed on the zeolite crystal ( Figure 1 a, b); there are also abundant mesoporous and microporous structures. MoW@H-ZSM-5 multi-level pore catalytic material still has abundant macroporous structure ( Figure 1 c, d), mesoporous structure and microporous structure, indicating that after the active center is introduced, the multi-level pore structure is completely preserved and not destroyed. The multi-level pore structure can effectively promote the diffusion and transmission of macromolecular materials and improve the conversion efficiency. In addition, in order to explore the dispersion of Mo and W elements in MoW@H-ZSM-5, SEM-Mapping was used for scanning, and it can be found that Mo and W elements were successfully introduced into the catalyst and were highly dispersed, providing rich active sites for MoW@H-ZSM-5 multi-level pore catalytic materials.
[0057] (2) Transmission electron microscopy (TEM) analysis
[0058] In order to further confirm the structure of the acidic oxide molecular sieve multi-level porous catalytic material, the H-ZSM-5 multi-level porous support prepared in Example 1 and the 0.13MoW@H-ZSM-550℃ multi-level porous catalytic material provided in Example 1 were characterized by TEM. The results are as follows: Figure 2 shown.
[0059] Figure 2 (a, c) are transmission electron micrographs of the H-ZSM-5 multi-level porous carrier. It can be clearly seen that there are abundant macropores on the surface and inside the crystals of the zeolite carrier, and the pore structure is evenly arranged with almost the same pore size. Figure 2 (b, d) are TEM images of the MoW@H-ZSM-5 catalyst. It can be seen that after the introduction of the active centers MoO3 and WO3, the multi-level pore structure of the MoW@H-ZSM-5 catalyst is well preserved and not destroyed. The TEM results further illustrate that the acidic oxide molecular sieve multi-level pore catalytic material MoW@H-ZSM-5 of the present invention has a good multi-level pore structure.
[0060] (3) Nitrogen adsorption-desorption analysis
[0061] The H-ZSM-5 multi-level porous carrier prepared in Example 1 and the 0.13MoW@H-ZSM-550℃ multi-level porous catalytic material provided in Example 1 were subjected to nitrogen adsorption-desorption measurement. The results are as follows: Figure 3 shown.
[0062] from Figure 3 It can be seen that both samples show typical type IV isotherms. At lower relative pressures, the adsorption amount rises rapidly, indicating the presence of micropores in both samples. When the relative pressure P / P0 is in the range of 0.4-0.9, all samples show an H2-type hysteresis loop, which may be due to the mesopores formed by the mutual accumulation of zeolites. When P / P0>0.9, the hysteresis loop changes from H2 to H3, indicating the presence of macropores in the catalyst. Among them, the specific surface area of the H-ZSM-5 multi-level porous carrier is 400-500m 2 / g, pore volume is 0.12-0.18cm 3 / g, and the average pore size is 4.87-9.18nm. The specific surface area of the acidic oxide molecular sieve multi-level pore catalytic material MoW@H-ZSM-5 is 290-310m 2 / g, pore volume is 0.10-0.11cm 3 / g, the average pore size is 4.61-4.82nm; the specific surface area of the multi-level porous catalytic material 0.13MoW@H-ZSM-5-550℃ is the largest, which is 293m 2 / g, pore volume 0.11cm 3 / g, and the average pore size is 4.68nm.
[0063] (4) Acidity analysis
[0064] The acidity of the H-ZSM-5 multi-level porous carrier prepared in Example 1 and the 0.13MoW@H-ZSM-550℃ multi-level porous catalytic material provided in Example 1 was measured by NH3-TPD method. The results are as follows: Figure 4 shown.
[0065] The H-ZSM-5 multi-level porous carrier has a weak desorption peak caused by NH3 desorption between 0-200℃, and the acid amount is 0.34mm / g, indicating that the H-ZSM-5 multi-level porous carrier has weak acidity. After the introduction of Mo and W active species, the acid amount of MoW@H-ZSM-5 increased significantly, and the total acid amount was 1.11mmol / g. Three desorption peaks appeared in the NH3-TPD curve of the catalyst MoW@H-ZSM-5, indicating that weak acid sites, medium-strong acid sites and strong acid sites exist in the catalyst at the same time, and the corresponding acid amounts are 0.65mm / g, 0.38mmol / g and 0.08mmol / g, respectively. The NH3-TPD results show that the introduction of Mo and W active centers can bring abundant acid sites to the multi-level porous material, thereby improving the catalytic activity of the multi-level porous material.
[0066] (5) Py-IR analysis
[0067] In order to determine the type of acid sites in the MoW@H-ZSM-5 catalyst, the Py-IR of the 0.13MoW@H-ZSM-5-550°C multi-level catalytic material provided in Example 1 was measured at different desorption temperatures. The results are shown in Figure 5. In the Py-IR spectrum of the multi-level catalytic material, at 1447 cm -1 and 1608cm -1 Two characteristic absorption peaks appeared at 1541cm -1 and 1637cm -1 The two characteristic peaks at 1489cm -1 The characteristic peaks appearing at can be attributed to the integration of Lewis acid sites and Bronsted acid sites. In addition, the characteristic peaks of Lewis and Bronsted acid sites can still be detected at a desorption temperature of 300°C, indicating that the acid sites of the multi-level porous catalytic material are relatively strong. Py-IR results show that the MoW@H-ZSM-5 multi-level porous catalytic material contains Lewis acid sites and Bronsted acid sites, which can catalyze different chemical reactions and have a coupled catalytic effect.
[0068] Example 2W@H-ZSM-5 and its preparation method,
[0069] This embodiment provides an acidic oxide molecular sieve multi-level porous catalytic material W@H-ZSM-5 and a preparation method thereof, which is basically the same as the MoW@H-ZSM-5 and a preparation method thereof provided in Example 1, mainly different in step S3: In this embodiment, step S3 includes dissolving 10.5gH3PO4·12WO3·XH2O in 80mL water, adding 10g H-ZSM-5 multi-level porous carrier, and stirring at room temperature for 12h. Then filter and dry at 80°C for 18h. The dried solid is placed in a muffle furnace and calcined at 550°C for 8h. Finally, 19.8g W@H-ZSM multi-level porous catalytic material is obtained, and the molar ratio of W / Si therein is 0.13. The W@H-ZSM multi-level porous catalytic material provided in this embodiment can be expressed as: 0.13W@H-ZSM-550℃.
[0070] Example 3 Mo@H-ZSM-5 and its preparation method,
[0071] This embodiment provides an acidic oxide molecular sieve multi-level porous material Mo@H-ZSM-5 and a preparation method thereof, which is basically the same as the MoW@H-ZSM-5 and a preparation method thereof provided in Example 1, except that step S3 is different: in this embodiment, step S3 includes: 7.7 g (NH4)6Mo7O 24 ·4H2O was dissolved in 80mL water, 10g H-ZSM-5 multi-level porous carrier was added, and stirred at room temperature for 12h. Then it was filtered and dried at 80℃ for 18h. The dried solid was placed in a muffle furnace and calcined at 550℃ for 8h. Finally, 16.2g Mo@H-ZSM multi-level porous catalytic material was obtained, and the molar ratio of Mo / Si was 0.13. The Mo@H-ZSM multi-level porous material provided in this embodiment can be marked as: 0.13Mo@H-ZSM-550℃.
[0072] Example 4-9 MoW@H-ZSM-5 and its preparation method
[0073] Examples 4-9 provide a MoW@H-ZSM-5 multi-level porous catalytic material, whose structure and preparation method are basically the same as those of Example 1, except that H3PO4·12WO3·XH2O and (NH4)6Mo7O used in step S3 24 The calcination temperature in this step varies with the mass of 4H2O, as shown in Table 1 below.
[0074] Table 1 Important process parameters of step S3 in the preparation of MoW@H-ZSM-5 porous catalytic materials
[0075] Example Mo+W / Si molar ratio <![CDATA[H3PO4·12WO3·XH2O]]> <![CDATA[(NH4)6Mo7O 24 ·4H2O]]> Calcination temperature Example 4 0.10 4.03g 2.95g 550℃ Example 5 0.16 6.43 g 4.72g 550℃ Example 6 0.13 5.23 g 3.83g 700℃ Example 7 0.13 5.23 g 3.83g 850℃ Example 8 0.13 4.96g 4.02g 550℃ Example 9 0.13 4.73g 4.18g 550℃
[0076] Among them, the W:Mo molar ratio in Examples 4-7 is 1:1, the W:Mo molar ratio in Example 8 is 1:1.1, and the W:Mo molar ratio in Example 9 is 1:1.2.
[0077] Comparative Example 1
[0078] This comparative example provides a 0.13MoW@ZSM-5-550℃ catalytic material, which is basically the same as the 0.13MoW@H-ZSM-5-550℃ multi-level porous catalytic material provided in Example 1, with the main difference being that this comparative example uses a commercially available conventional ZSM-5 molecular sieve as a carrier instead of the H-ZSM-5 multi-level porous carrier in step S3 of Example 1, and other methods and parameters are the same.
[0079] Example 10 Application of acidic oxide molecular sieve multi-level pore catalytic material in oil-to-biofuel conversion
[0080] This embodiment provides the application of the acidic oxide molecular sieve catalytic material prepared by Examples 1-9 and Comparative Example 1 in oil-to-biofuel conversion. The specific method includes: using soybean oil and methanol as raw materials to prepare biodiesel using an intermittent high-pressure reactor, adding 500g soybean oil and 640g methanol into a reactor, and then adding the above acidic oxide molecular sieve catalytic material of 8wt% of the mass of soybean oil, stirring the reaction at 130°C for 8h, and the stirring speed is 460rpm. After the reaction is completed, cool to room temperature, filter the acidic oxide molecular sieve catalytic material, reduce pressure to evaporate excess methanol, and use the evaporated methanol. Then, separate glycerol by centrifugation, and detect the oil conversion rate of the product by gas chromatography, as shown in Table 2.
[0081] Table 2 Oil conversion rate of soybean oil catalyzed by different porous materials
[0082] sample composition Oil conversion rate (%) Example 1 0.13MoW@H-ZSM-5-550℃ 94.2 Example 2 0.13W@H-ZSM-5-550℃ 47.8 Example 3 0.13Mo@H-ZSM-5-550℃ 89.4 Example 4 0.10MoW@H-ZSM-5-550℃ 88.4 Example 5 0.16MoW@H-ZSM-5-550℃ 90.2 Example 6 0.13MoW@H-ZSM-5-700℃ 83.4 Example 7 0.13MoW@H-ZSM-5-850℃ 52.6 Example 8 0.13MoW@H-ZSM-5-550℃ 91.5 Example 9 0.13MoW@H-ZSM-5-550℃ 89.7 Comparative Example 1 0.13MoW@ZSM-5-550℃ 85.4
[0083] Combined with Table 2, from the oil conversion rates of Examples 1-3 and Comparative Example 1, the 0.13MoW@H-ZSM-5-550℃ multi-level pore catalytic material provided in Example 1 has a high catalytic activity, and the Mo and W active components have a certain synergistic effect. In addition, the multi-level macropore-mesopore-micropore structure has a significant effect on improving the catalytic performance of the catalytic material in the process of converting oil to biofuel.
[0084] Judging from the oil conversion rates of Examples 1 and 4-5, the oil conversion rate in the MoW@H-ZSM-5 multi-level porous catalytic material first increases and then decreases with the increase of the molar ratio of the active component Mo+W / Si, and the oil conversion rate reaches the highest point when the molar ratio is 0.13.
[0085] From the oil conversion rates of Examples 1 and 6-7, the conversion rate of the MoW@H-ZSM-5 multi-level porous catalytic material decreases with the increase of the calcination temperature during its formation, and at a calcination temperature of 550°C, the oil conversion rate reaches a maximum of 94.2%.
[0086] Example 11 Application of MoW@H-ZSM multi-level pore catalytic material in the conversion of waste oil into biofuel
[0087] In this embodiment, waste cooking oil and methanol are used as raw materials, and biodiesel is prepared by an intermittent high-pressure reactor. 500g of waste cooking oil and 640g of methanol are added to the reactor, and then 8wt% of the mass of soybean oil is added to the 0.13MoW@H-ZSM-5-550℃ multi-level catalytic material provided in the above embodiment 1 or the 0.13MoW@ZSM-5-550℃ multi-level catalytic material provided in comparative example 1, and the reaction is stirred at 130℃ for 8h, and the stirring speed is 460rpm. After the reaction is completed, it is cooled to room temperature, the multi-level catalytic material is filtered, and the excess methanol is evaporated under reduced pressure, and the evaporated methanol is used. Then, glycerol is separated by centrifugation, and the oil conversion rate and free fatty acid conversion rate of the product are detected by gas chromatography, and the results are shown in Table 3.
[0088] Table 3 Oil conversion rate of waste cooking oil catalyzed by multi-level pore catalytic materials
[0089]
[0090] Example 11: Recycling of Mo / V@H-Al2O3 multi-level catalytic materials in oil-to-biofuel conversion
[0091] The 0.13MoW@H-ZSM-5-550℃ multi-level porous catalytic material provided in Example 1 was recovered, washed three times with cyclohexane and methanol respectively, and dried, and then soybean oil and waste cooking oil were used as raw materials respectively, and the methods provided in Examples 10 and 11 were repeated to prepare biodiesel in an intermittent high-pressure reactor. The catalytic effect of repeated use is shown in Table 4. Among them, the water content in the waste cooking oil in this example is: 1.8 mg / g, and the acid value is: 20.6 mg (KOH) / g.
[0092] Table 4 Oil conversion rate of MoW@H-ZSM-5 multi-level pore catalytic material reuse (%)
[0093] raw material Use once Use 2 times Use 3 times Use 4 times Use 5 times Soybean Oil 94.2 93.1 90.2 86.5 82.7 Waste cooking oil 92.7 89.8 84.3 80.2 76.2
[0094] Table 4 shows that the catalytic activity of MoW@H-ZSM-5 multi-level porous catalytic material gradually decreases with the increase of the number of reuses. After being reused 4 times, the biofuel conversion rate of MoW@H-ZSM multi-level porous catalytic material is still over 80%, which has good reuse performance.
[0095] Therefore, the acidic oxide molecular sieve multi-level porous material provided in the embodiment of the present invention is mainly prepared by a hydrothermal method combined with a calcination process to prepare a multi-level porous molecular sieve solid acid catalytic material with a macroporous structure. First, MSPs are synthesized as a template; then MSPs are impregnated with TPAOH to provide a zeolite microporous template and an alkalinity source; finally, an intracrystalline macroporous zeolite molecular sieve H-ZSM-5 with a classic morphology and good interconnection is prepared by evaporation-assisted crystallization. Compared with the traditional zeolite molecular sieve ZSM-5, the macroporous structure possessed by H-ZSM-5 can reduce the transmission and diffusion restrictions of macromolecular reactants, has better resistance to coke formation, and can extend the life of the catalyst. In addition, the zeolite molecular sieve H-ZSM-5 prepared in the embodiment of the present invention overcomes the problems of poor thermal stability of traditional zeolite nanocrystals and difficulty in recovery from the reaction mixture. By loading the metal oxides MoO3 and WO3 onto H-ZSM-5, the solid catalyst can be given a stronger acidity. The finally synthesized heterogeneous solid acid catalytic materials W@H-ZSM-5 and MoW@H-ZSM-5 have good stability and catalytic performance. They are applied to biofuel production and can convert pure materials or waste oil into biofuel in one step. They have good biofuel production efficiency. The heterogeneous molecular sieve solid acid catalytic materials have high reusability.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. An acidic oxide molecular sieve multi-level pore catalytic material, characterized in that: It includes a H-ZSM-5 multi-level porous carrier and an acidic oxide loaded on the H-ZSM-5 multi-level porous carrier, wherein the H-ZSM-5 multi-level porous carrier is a zeolite with an ordered macropore-mesopore-micropore multi-level pore structure, and the acidic oxide mainly includes WO3 or mainly includes WO3 and MoO3.
2. The acidic oxide molecular sieve multi-level porous catalytic material according to claim 1, characterized in that: The molar ratio of the metal element in the acidic oxide to the silicon element in the H-ZSM-5 multi-level porous carrier is 0.1-0.2, and the acidic oxide is composed of WO3 and MoO3, and the molar ratio of WO3 to MoO3 is 1:1-1.
2.
3. The acidic oxide molecular sieve multi-level porous catalytic material according to claim 1 or 2, characterized in that: The H-ZSM-5 multi-level porous carrier has a specific surface area of 400-500 m² / g and a pore volume of 0.12-0.18 cm 3 / g, and the average pore size is 4.87-9.18 nm.
4. A method for preparing the acidic oxide molecular sieve multi-level porous catalytic material according to claim 1, comprising the steps of: Impregnation treatment: using an acidic oxide precursor and a H-ZSM-5 multi-level porous carrier as raw materials, the acidic oxide precursor is loaded onto the H-ZSM-5 multi-level porous carrier by an impregnation method to obtain H-ZSM-5 loaded with the acidic oxide precursor; wherein, The acidic oxide precursor mainly includes H3PO4·12WO3·XH2O, or mainly includes H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 4H2O mixture; Calcination treatment: calcining the H-ZSM-5 loaded with the acidic oxide precursor at 500-700° C. to obtain the acidic oxide molecular sieve multi-level pore catalytic material; During the calcination process, the precursors H3PO4·12WO3·XH2O and (NH4)6Mo7O 24 ·4H2O is decomposed to form acidic oxides WO3 and MoO3.
5. The preparation method according to claim 4, characterized in that The calcination treatment step includes: calcining the H-ZSM-5 loaded with the acidic oxide precursor at 550-600° C. for 6-10 h to obtain the acidic oxide molecular sieve multi-level pore catalytic material.
6. The preparation method according to claim 4 or 5, characterized in that: The impregnation step includes: impregnating the H-ZSM-5 multi-level porous support into an acidic oxide precursor solution for 8-12 hours by an impregnation method, and then performing a drying process to obtain the H-ZSM-5 loaded with the acidic oxide precursor.
7. The preparation method according to claim 6, characterized in that: The preparation method of the H-ZSM-5 multi-level porous carrier comprises: The mesoporous silica spheres and Al(NO3)3·9H2O solution were uniformly mixed, and then dried at 30-50°C for 2-4 h to obtain a mesoporous silica sphere dry powder loaded with aluminum nitrate, wherein the particle size of the mesoporous silica spheres was 240-260 nm, the specific surface area was 321-348 m² / g, and the pore volume was 0.12-0.14 cm 3 / g; The dry powder is uniformly mixed with a tetrapropylammonium hydroxide aqueous solution having a concentration of 30 wt%-50 wt% at 30-60° C. for reaction for 1.5-3 h, so that aluminum hydroxide is in situ deposited on the mesoporous silica spheres, and after a crystallization treatment assisted by thermal evaporation for 48-72 h, filtered, and dried at 70-100° C. for 12-24 h to obtain mesoporous silica spheres loaded with aluminum hydroxide spheres; Then, the aluminum hydroxide-loaded mesoporous silica spheres are calcined at a temperature of 500-600° C. for 4-6 h.
8. The preparation method according to claim 7, characterized in that The preparation method of the mesoporous silica spheres comprises: adding hexadecyltrimethylammonium bromide to an ethanol-water solution, stirring to dissolve, then adding an ammonia solution, and stirring at room temperature for 1-2 hours; then adding tetraethyl orthosilicate, and continuing to stir at room temperature for 1-2 hours to obtain a white precipitate; the obtained precipitate is dried at 70-100°C overnight, and then calcined at 500-600°C for 6-8 hours to obtain the mesoporous silica spheres.
9. Use of the acidic oxide molecular sieve multi-level pore catalytic material according to any one of claims 1 to 3 in catalyzing oil to produce biofuel, wherein: The amount of the multi-level porous catalytic material used is 6-10 wt % of the mass of the oil.
10. The use according to claim 9, characterized in that: The oil is waste oil, and the water content of the waste oil is 0-5.8%, and the free fatty acid content is 0-62.7 mg (KOH) / g.